Indeks Kerukunan Umat Beragama Kota Lubuklinggau Tahun 2019 - Muhammad Yunus; Ngimadudin Ngimadudin; Yesi Arikarani; Ismurijal Umar (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2019)
This research is a research that measures harmony of religious harmony in Lubuklinggau City. In the context of the City of Lubuklinggau as a city that has a plurality of religions, this can actually be a capital in regional development. Then the study to be explored is How high is the religious harmony index of the city of Lubuklinggau in 2019? The quantitative research methods used in the study approach pattern with descriptive statistics and inferential statistics. Descriptive statistics are used to explain the characteristics of the data which include, mode, mean and standard deviation of each variable. After the field survey and calculation are done, the results of the research, the 2019 Survey conducted by FKUB of Lubuklinggau City found that the harmony index of Lubuklinggau city in 2019 was at 5.52, this figure was 22 points higher than the STARA INSTITUT survey in 2017. This survey also rejects the null hypothesis (H0) at the 0.05 significance level. This means that H0: µ = 5.30 cannot be generalized to the population.